Kritik terhadap Patriarki: Pendekatan Sosiologis Sastra Cerpen “Jemari Kiri” Karya Djenar Maesa Ayu - Abas, Novita; Bagtayan, Zilfa A. (Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study aims to reveal varios social issues contained in the short story Jemari Kiri by Djenar Maesa Ayu. In addition, this study also aims to reveal the existence of a patriarchal system that occurs in this short story. To reveal the above, th author uses a sociological literary approach, in analysing the short story. This study uses a qualitative method and is supported by a literature study. Through a sociological literary approach, the author analyses the contens of the entire short story. The results of the study indicate that there is a patriarchy that is detrimental to women in this short story.